Democratic leadership practices in Edo State Nigeria: A justification for a Biomimetic-based democratic alternative - T. I. 1, Ugwoegbu; Fashae G. C.2, Abey (Universitas PGRI Madiun, 2023)
This article - the last of a two-part assessment of leadership practices in community development processes, noted that since Nigeria’s independence 6 decades ago, only the past 2 decades has experienced uninterrupted democracy. Considering the importance of ideal democratic processes in actualizing progressive community development, the paper examined participation in politics, relative to leadership among geese to justify the need for nature-based alternative leadership practices in egalitarian developing communities. Analysis of empirical evidences from literature was used to evaluate key leadership issues, discuss political situations, and models of citizens’ participation across Edo State communities in Nigeria. Observed democratic leadership in the study area turned out as “practices that are alien to democracy” because it lacked the basic tenets of democracy. Several indices of participation in politics were articulated and matched against practices among the geese towards articulating a Biomimetic-based Democratic Leadership Practices for community progression. Recommendations were made and implication drawn.